Political Jawara of Local Moslem Elits Among Banten Oligarchy In Indonesia After The New Order Era - Irfani, Fahmi; Nafiudin, Imam; Jamaluddin, Wan (JURNAL JAWI, 2018)
This paper focuses on the dynamic portrait of politics among moslem elits and Jawara in Indonesia, especially in the western tip of Java Island (Banten Province). Using a critical analysis in its document research, this study enriched by socio-political methods and socio-anthropological approaches. The study issued that the collapsed of the New Order (orde baru) regime and the start of a decentralized system of regional autonomy caused the increasing of local moslem elites commonly called Jawara as an informal leader in Banten due to the malfunctions of the state itself. It was clearly enough can be seen from the political and economic system in Banten controlled by the elites moslem local (Jawara) showing the portrait of local oligarchy in Banten; in which the institutional government leads only by the elites moslem local and certain family clan. All those things cause the economic policies and government affairs taken over by the elites (Jawara). The political constellation in Banten become more interesting when the moslem elites local itself are still giving a huge influence in determining the political orientation for Banten society.